Representation and resistance in Restoration Scotland: the political thought of James Stewart of Goodtrees (1635–1713). (4th May 2018) - McIntyre, Neil
SUMMARY: This article presents a Scottish case study of early modern ideas on parliamentary representation and popular political participation. By scrutinizing the context and content of a treatise published in 1669 by the lawyer James Stewart of Goodtrees, the article seeks to demonstrate that views had shifted on the nature of the Scottish Parliament. In addition, it is argued that the promulgation of Scotland's covenants – that is, the National Covenant (1638) and the Solemn League and Covenant (1643) – unwittingly created space for the development of popular political engagement. However, the implications of this were not fully realized until a group of middling and lower class men rose in arms to uphold the Covenants after their rescission in law by parliamentary statute in 1661.